CUTTING AND GRAFTING AS INFLUENCING FACTORS ON THE INITIAL GROWTH AND PRODUCTION OF ABIU FRUIT IN FIELD CONDITIONS - Nacata, Guilherme [UNESP]; Bagatim, Amanda Garcia [UNESP]; Andrade, Renata Aparecida de [UNESP] (Interciencia, 2016)
This study aimed to verify if there are differences in initial development of seedlings of abiu (Pouteria caimito) originated from two propagation methods (cutting and grafting), in field conditions. Before and after pruning, monthly evaluations were performed of plant height (cm), stem diameter (cm), canopy diameter on the line and in the planting spacing (cm), also recording the distance between of plants in the field and the beginning of fruiting. The data were analyzed in a 2x2 factorial (method of propagation to obtain the seedlings x evaluation time), evaluating 30 seedlings per treatment in a design with subdivided parcels, considering as the main treatments the two methods of obtaining seedlings (cuttings and grafting) and as secondary treatment the time of evaluation (before and after pruning). The results in field conditions allow to conclude that there is lower post-planting mortality rate, higher early flowering and fruiting, and best answers, after pruning of plants obtained from cuttings.